2020
DOI: 10.1596/33883
|View full text |Cite
|
Sign up to set email alerts
|

Invention and Global Diffusion of Technologies for Climate Change Adaptation

Abstract: This work is a product of the staff of The World Bank and the Global Facility for Disaster Reduction and Recovery (GFDRR) with external contributions. The findings, analysis and conclusions expressed in this document do not necessarily reflect the views of any individual partner organization of The World Bank, its Board of Directors, or the governments they represent.Although the World Bank and GFDRR make reasonable efforts to ensure all the information presented in this document is correct, its accuracy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In their paper, they use data from 31 European countries and find essentially no evidence that carbon taxes have had a negative effect on GDP growth or employment. Dechezleprêtre et al (2014) found that knowledge spillovers-measured by patent citations-are significantly greater for 'clean' technologies than for 'dirty' technologies and that 'clean' patents tend to be cited by more prominent patents. This provides some empirical support for the Acemoglu et al (2012) results.…”
Section: Carbon Taxesmentioning
confidence: 96%
“…In their paper, they use data from 31 European countries and find essentially no evidence that carbon taxes have had a negative effect on GDP growth or employment. Dechezleprêtre et al (2014) found that knowledge spillovers-measured by patent citations-are significantly greater for 'clean' technologies than for 'dirty' technologies and that 'clean' patents tend to be cited by more prominent patents. This provides some empirical support for the Acemoglu et al (2012) results.…”
Section: Carbon Taxesmentioning
confidence: 96%
“…However, the rapid growth of innovation in the PRC and the Republic of Korea is notable. Together, these two countries produced less than 4% of all adaptation inventions in 1995 and increased their shares to 8.9% and 7.8%, respectively, in 2015 (Dechezlepretre et al 2020).…”
Section: Objective Of Adb Operationsmentioning
confidence: 99%
“…Adaptation solutions have also been included in international innovation and patent registers. Dechezlepretre et al (2020) examined the trend in adaptation innovation, measured by the number of registered patents, during a 20-year period covering 1995-2015. As shown in Figure 5, the rate of innovation activity in pure climate change adaptation technologies since 1995 has been constant.…”
Section: Objective Of Adb Operationsmentioning
confidence: 99%
“…The Y02 class is always a secondary classification and can be added to patent families from a broad set of technologies, from those aimed at reducing drag on airplanes to those aimed at treating diseases whose impact may be exacerbated by climate change (Veefkind et al, 2012, Haščič andMigotto, 2015). This class (and its subclasses) are commonly used as filters to study patented technological developments within specific domains related to both the mitigation of climate change, such as cleaner transport (Aghion et al, 2016, Barbieri, 2016 and energy production (Sun et al, 2021, Persoon et al, 2020, and our adaptation to the inevitable and wide-ranging environmental challenges we will face in the near future (Dechezleprêtre et al, 2020, Hötte et al, 2021. As such, we believe this technology class comprises a suitable microcosm within which we can effectively demonstrate the application of multilayer network methods to patent citation networks.…”
Section: Datamentioning
confidence: 99%